Development of Colloidal Silver-based Mercury Sensors in Whitening Cream - Muhammad Hilmi Afthoni; Sherly Yunita; Eva Monica (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Mercury, a hazardous heavy metal known for its toxicity to the human body, finds application in cosmetics due to its capacity to inhibit melanin formation. Traditional mercury analysis relies on resource-intensive and time-consuming instrumentation. Objective: This study aims to devise cost-effective and practical sensors for mercury detection. Methods: The sensor development process involves immobilizing the sensor onto paper, reacting it with mercury, scanning the outcome using a scanner, and subsequently quantifying RGB values using the ImageJ software. Results: Optimization of reagent concentrations gave a ratio of methylene blue, AgNO3, gallic acid, and ascorbic acid at 0.5:7:1.5:1 generating the best results. Additionally, pH optimization within the range of 5 to 9 demonstrates stability without necessitating the inclusion of a buffer solution. Notably, the blue variant exhibits superior responsiveness during concentration optimization. Characterization of the sensor reveals a response time of 3 minutes and minimal interference of 2.145% from other substances. The sensor exhibits a linearity range of 0.5-250 ppm, regression equation y = 8.603x + 21.124, an R-value of 0.994, and an exceedingly low p-value of 6.9924589548512 x 10-9. The sensor boasts a limit of detection (LOD) of 0.206 and a limit of quantification (LOQ) of 0.265, indicative of its precision. Further assessments reveal a percent relative standard deviation (% RSD) precision of 2.017% and a recovery rate of 96.14%. Conclusion: The sensor has exhibited stability for over one month under room temperature storage conditions. A comparison between the UV-Vis spectrophotometer and the sensor signifies no significant difference between the two methods.